Effect of concentrated light on morphology and vibrational properties of boron and tantalum mixtures - Sartinska, Lina; Chkhartishvili, Levan; Voynich, Eugen; Eren, Tarik; Frolov, Gennadiy; Altay, Esra; Murusidze, Ivane; Tsagareishvili, Otar; Gabunia, Domenti; Maisuradze, Nodar (ELSEVIER SCI LTD, 2018)
Heating a mixture of boron (impurities: carbon similar to B50C2, boric acid - H3BO3) and tantalum (Ta) powders in nitrogen flow in a xenon high-flux optical furnace was performed. As-received powder composed of h-BN, H3BO3, TaB2, B9H11 and a number of other phases including beta-rhombohedral boron, apparently, heavily doped with Ta. FT-IR examination of any sample of the material reveals the complicated vibration spectrum containing, in particular, an absorption band near 2260 cm(-1). The shapes of these bands are different for samples because powders were synthesized at different temperatures. Known, that in beta-rhombohedral boron lattice, there are nano-sized voids of different types, which allow an accommodation of single atoms or small groups of atoms. Theoretical calculations performed by the method of quasi-classical type yields the same value, 2260 cm(-1), for the vibrations frequency of Ta atoms in D-type crystallographic voids in beta-rhombohedral boron lattice. Since, Ta atoms are known to prefer accommodation just in D-voids the experimentally detected bands can be identified with localized vibrations of Ta atoms.
Keywords: Condensed matter physics; Materials science; Nanotechnology; CATALYST-FREE SYNTHESIS; ENERGIES; WHISKERS; CRYSTAL; GROWTH; Science & Technology - Other Topics